Feminist pedagogy as a new initiative in the education of South African teachers - Sonja Schoeman (Koers : Bulletin for Christian Scholarship, 2015)
Not much has been published about feminist pedagogy and teacher education in South Africa. The purpose of this article is to introduce the above to the South African education fraternity, where it has not yet found a comfortable home. The problem of the study focues on two issues: the lack of an alternative teacher education perspective and experience in South Africa, and the possibility of teacher education for the new gender order, and a revival of the gender equity debate.  The purpose of the study is to reflect on the gendered (patriarchal) teacher education models, enhance the pre-service teachers' understanding of the power relations in education, and argue the case for the inclusion of feminist pedagogy in teacher education programmes.  A qualitative conceptual document analysis was used as research design. The article is concluded with an exemplar teacher education model in which student teachers are introduced to a critical study of learning to teach (feminist pedagogy), and a feminist classroom setting.